2002
DOI: 10.1001/jama.288.16.2023
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR 677C→T Polymorphism and Risk of Coronary Heart Disease

Abstract: Individuals with the MTHFR 677 TT genotype had a significantly higher risk of CHD, particularly in the setting of low folate status. These results support the hypothesis that impaired folate metabolism, resulting in high homocysteine levels, is causally related to increased risk of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
482
7
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(531 citation statements)
references
References 86 publications
27
482
7
15
Order By: Relevance
“…The genes that encode the proteins/enzymes related to folate uptake and metabolism include many polymorphisms, among which MTHFR C677T, CBS 844ins68, GCPII H475Y, MTR A2756G, and MTRR A66G are known to affect folate and vitamin B12 intake (Uauy et al 2014). Genetic polymorphisms related to the folate pathway have been shown to be associated with functional implications and specific conditions including NTDs (van der Linden et al 2006), cardiovascular disease (Klerk et al 2002), and some types of cancers, such as colorectal, breast, and lung cancers (Lee 2009). To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake.…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%
“…The genes that encode the proteins/enzymes related to folate uptake and metabolism include many polymorphisms, among which MTHFR C677T, CBS 844ins68, GCPII H475Y, MTR A2756G, and MTRR A66G are known to affect folate and vitamin B12 intake (Uauy et al 2014). Genetic polymorphisms related to the folate pathway have been shown to be associated with functional implications and specific conditions including NTDs (van der Linden et al 2006), cardiovascular disease (Klerk et al 2002), and some types of cancers, such as colorectal, breast, and lung cancers (Lee 2009). To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake.…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%
“…Of particular interest, extensive evidence has led to a number of meta-analyses reporting a strong association between this polymorphism and CVD, particularly stroke (73)(74)(75)(76) . It has been estimated that individuals with the MTHFR 677TT polymorphism have a 14-21 % increased risk of CHD (75,77,78) .…”
Section: Riboflavin C 1 Metabolism and Cvd Riskmentioning
confidence: 99%
“…Although riboflavin is required for numerous metabolic reactions its role (in the form of FAD) as a cofactor for the folatemetabolising enzyme, methylenetetrahydrofolate reductase (MTHFR) has recently received particular attention. Homozygosity (MTHFR 677TT genotype) for a common polymorphism in MTHFR, affecting over 10 % of the UK and Irish populations and up to 32 % of other populations worldwide (2) , has been associated with an increased risk of CVD (3) and more recently with hypertension (4) . Emerging evidence from intervention trials supports a novel role for riboflavin supplementation in protecting against hypertension specifically in individuals with the MTHFR 677TT genotype (5)(6)(7) .…”
mentioning
confidence: 99%
“…Several meta-analyses to date have demonstrated an increased risk of CVD in individuals with the TT genotype compared to those without this genetic variant (1,2,(20)(21)(22) (Table 1). Those studies which assessed the risk of CHD events estimated a 14-16% higher risk in individuals with the TT genotype compared to those with the CC genotype (20,23) .…”
Section: Association Between the Mthfr 677c T Polymorphism And Cvd Riskmentioning
confidence: 99%